Extracellular vesicles as surrogates for drug metabolism and clearance: promise vs. reality - Gagliardi, Anna; Bajraktari-Sylejmani, Gzona; Barocelli, Elisabetta; Weiß, Johanna; Rigalli, Juan Pablo (Life, 2023)
Drug-metabolizing enzymes (DMEs) and transporters play a major role in drug efficacy and safety. They are regulated at multiple levels and by multiple factors. Estimating their expression and activity could contribute to predicting drug pharmacokinetics and their regulation by drugs or pathophysiological situations. Determining the expression of these proteins in the liver, intestine, and kidney requires the collection of biopsy specimens. Instead, the isolation of extracellular vesicles (EVs), which are nanovesicles released by most cells and present in biological fluids, could deliver this information in a less invasive way. In this article, we review the use of EVs as surrogates for the expression and activity of DMEs, uptake, and efflux transporters. Preliminary evidence has been provided for a correlation between the expression of some enzymes and transporters in EVs and the tissue of origin. In some cases, data obtained in EVs reflect the induction of phase I-DMEs in the tissues. Further studies are required to elucidate to what extent the regulation of other DMEs and transporters in the tissues reflects in the EV cargo. If an association between tissues and their EVs is firmly established, EVs may represent a significant advancement toward precision therapy based on the biotransformation and excretion capacity of each individual.